Promoter of CaZF, a Chickpea Gene That Positively Regulates Growth and Stress Tolerance, Is Activated by an AP2-Family Transcription Factor CAP2 - Jain, Deepti (Public Library of Science, 2013)
Plants respond to different forms of stresses by inducing transcription of a common and distinct set of genes by concerted actions of a cascade of transcription regulators. We previously reported that a gene, CaZF encoding a C2H2-zinc finger family protein from chickpea (Cicer arietinum) imparted high salinity tolerance when expressed in tobacco plants. We report here that in addition to promoting tolerance against dehydration, salinity and high temperature, the CaZF overexpressing plants exhibited similar phenotype of growth and development like the plants overexpressing CAP2, encoding an AP2-family transcription factor from chickpea. To investigate any relationship between these two genes, we performed gene expression analysis in the overexpressing plants, promoter-reporter analysis and chromatin immunoprecipitation. A number of transcripts that exhibited enhanced accumulation upon expression of CAP2 or CaZF in tobacco plants were found common. Transient expression of CAP2 in chickpea leaves resulted in increased accumulation of CaZF transcript. Gel mobility shift and transient promoter-reporter assays suggested that CAP2 activates CaZF promoter by interacting with C-repeat elements (CRTs) in CaZF promoter. Chromatin immunoprecipitation (ChIP) assay demonstrated an in vivo interaction of CAP2 protein with CaZF promoter.